Treatment decision satisfaction and regret after focal HIFU for localized prostate cancer - Westhoff, Niklas Christian; Ernst, Ramona; Kowalewski, Karl-Friedrich; Schmidt, Laura; Worst, Thomas; Michel, Maurice Stephan; Hardenberg, Jost von (World journal of urology, 2021)
Focal therapies (FTs) are investigated within prospective studies on selected patients treated for localized prostate cancer (PCa). Benefits are preservation of genitourinary function and reduced complications, but follow-up is elaborate and is associated with uncertainty as cancer-free survival appears to be lower compared to standard radical treatments. The aim of this study was to analyse patient-reported acceptance of FT and evaluate factors associated with treatment decision regret.
Published: 12 June 2020
Gesehen am 18.11.2021